Field performance of ultrasensitive and conventional malaria rapid diagnostic tests in southern Mozambique - Beatriz Galatas; Alfredo Mayor; Himanshu Gupta; Núria Balanza; Ihn Kyung Jang; Lidia Nhamussua; Wilson Simone; Pau Cisteró; Arlindo Chidimatembue; Humberto Munguambe; Francisco Saúte; Pedro Aide; et al. (Malaria Journal, 2020)
Abstract Background An ultrasensitive malaria rapid diagnostic test (RDT) was recently developed for the improved detection of low-density Plasmodium falciparum infections. This study aimed to compare the diagnostic performance of the PfHRP2-based Abbott Malaria Ag P. falciparum ultrasensitive RDT (uRDT) to that of the conventional SD-Bioline Malaria Ag P. falciparum RDT (cRDT) when performed under field conditions. Methods Finger-prick blood samples were collected from adults and children in two cross-sectional surveys in May of 2017 in southern Mozambique. Using real-time quantitative PCR (RT-qPCR) as the reference method, the age-specific diagnostic performance indicators of the cRDT and uRDT were compared. The presence of histidine-rich protein 2 (HRP2) and Plasmodium lactate dehydrogenase (pLDH) antigens was evaluated in a subset from dried blood spots by a quantitative antigen assay. pfhrp2 and pfhrp3 gene deletions were assessed in samples positive by RT-qPCR and negative by both RDTs. Results Among the 4,396 participants with complete test results, the sensitivity of uRDTs (68.2; 95% CI 60.8 to 74.9) was marginally better than that of cRDTs (61.5; 95% CI 53.9 to 68.6) (p-value = 0.004), while the specificities were similar (uRDT: 99.0 [95% CI 98.6 to 99.2], cRDT: 99.2 [95% CI 98.9 to 99.4], p-value = 0.02). While the performance of both RDTs was lowest in ≥ 15-year-olds, driven by the higher prevalence of low parasite density infections in this group, the sensitivity of uRDTs was significantly higher in this age group (54.9, 95% CI 40.3 to 68.9) compared to the sensitivity of cRDTs (39.2, 95% CI 25.8 to 53.9) (p-value = 0.008). Both RDTs detected P. falciparum infections at similar geometric mean parasite densities (112.9  parasites/μL for uRDTs and 145.5 parasites/μL for cRDTs). The presence of HRP2 antigen was similar among false positive (FP) samples of both tests (80.5% among uRDT-FPs and 84.4% among cRDT-FPs). Only one false negative sample was detected with a partial pfhrp2 deletion. Conclusion This study showed that the uRDTs developed by Abbott do not substantially outperform SD-Bioline Pf malaria RDTs in the community and are still not comparable to molecular methods to detect P. falciparum infections in this study setting.